Positive and Negative Effects of Online Games on Muslim Students Learning Motivation - Septiana, Yulda Dina; Tegar, Rizki; Kurniawan, Benni (Al-Kahfi: Jurnal Pendidikan Agama Islam, 2024)
Online games have become a necessity in modern society, especially among teenagers and adults. While they are primarily for entertainment and social interaction, they also impact the learning process. Online games have grown rapidly recently, especially in the world of e-sports. There are many variations or types of online games, such as PUBG, Domino Island, Free Fire, Poker, and other online games, which create engaging gameplay. The more engaging the game, the more people play it. Online games have become a new lifestyle for students and adults. The presence of online games has significantly eroded students' motivation to learn at school, resulting in a decline in the quality of learning. This study, however, is a crucial activity in the education system. This study aims to analyze the impact of online games on high schools. This study uses a survey method using quantitative research methods. This type of research uses a survey because in data collection, the author gathered information from respondents using a questionnaire as the primary method. Overall, the research findings show that the impact of Mobile Legends on student achievement is a major concern in MAN throughout West Pasaman, according to frequency and percentage calculations. The researcher found a 72% impact of the Mobile Legend game on students. Meanwhile, the decline in student learning achievement, according to the distributed questionnaire, reached 63%. Several activities that should be created to avoid the impact of Mobile Legend are extracurricular activities and homework, as well as strict supervision of students' smartphones. It is important to maintain balance in the approach taken by MAN schools in West Pasaman. Although extracurricular activities such as KSR, Scouts, Osim, Dramband, and Nasyid provide positive benefits, they must be managed wisely to prevent students from becoming exhausted, especially if they return home late at school. With a balanced approach, these schools can help students better manage their time, maintain focus on learning, and motivate them to achieve better academic results.